Censoring art silencing the artwork - Kennedy, Roisin; Coulter, Riann (International Library of Visual Culture, 2018)
Art is continuously subjected to insidious forms of censorship. This may be by the church to guard against moral degeneration, by the state to promote a specific political agenda or by the art market, to elevate one artist above another. Now, and in the last century, artwork that touches on ethnic, religious, sexual, national or institutional sensitivities is liable to be destroyed or hidden away, ignored or side-lined.